2010
DOI: 10.1007/s12033-010-9365-3
|View full text |Cite
|
Sign up to set email alerts
|

Clones Identification and Genetic Characterization of Garnacha Grapevine by Means of Different PCR-Derived Marker Systems

Abstract: This study uses PCR-derived marker systems to investigate the extent and distribution of genetic variability of 53 Garnacha accessions coming from Italy, France and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 29 publications
(35 reference statements)
3
38
0
Order By: Relevance
“…For example, the fingerprint of accession 7 revealed genetic diversity, thus confirming the greater phenotypic variability observed by ampelographic analysis. Indeed, it has to be noted that, as already reported in the literature, AFLP fingerprinting data are in agreement with the results obtained by ampelographic analyses when a high number of morphological characters are considered (Meneghetti et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…For example, the fingerprint of accession 7 revealed genetic diversity, thus confirming the greater phenotypic variability observed by ampelographic analysis. Indeed, it has to be noted that, as already reported in the literature, AFLP fingerprinting data are in agreement with the results obtained by ampelographic analyses when a high number of morphological characters are considered (Meneghetti et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The Italian accessions were 6 Tocai rosso from the Vicenza area, 8 Alicante from Sicily and Elba island, 4 Gamay perugino from Perugia province and 10 Cannonau from Sardinia. In order to verify the varietal identity, the analyses based on 11 SSR loci confirmed that only one SSR profile was obtained for the 53 accessions ( Figure 6) (Meneghetti, 2011).…”
Section: Garnacha Tintamentioning
confidence: 82%
“…The amplification products were resolved on ReproGel High-Resolution pre-made acrylamide-bisacrylamide solutions (8% w/v) (GE Healthcare) in modified TBE buffer and detected on a semiautomated DNA sequencer, the ALFexpress-II DNA Analysis System (Amersham Pharmacia Biotech). Markers were visualized automatically by the ALF-win Fragment Analyses 1.09 software and checked by Quantity One 4.6.7 and PD Quest Basic 8.0.1 software (Biorad) (Meneghetti, 2011).…”
Section: Intra-varietal Genetic Variabilitymentioning
confidence: 99%
See 2 more Smart Citations